Pengaruh Penguatan Moderasi Beragama Terhadap Sikap Toleran dan Prilaku Beragama Santri SMPIT Pondok Pesantren As-Syakur Kota Bengkulu - Anis Dian Mutiara (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aimed to, 1) examine the effect of strengthening religious moderation on the tolerant attitudes of students at As-Syakur Islamic Boarding School in Bengkulu City; 2) examine the effect of strengthening religious moderation on students’ religious behavior. The research employed a quantitative non-experimental method with a correlational approach. Data were collected using questionnaires and analyzed through basic assumption tests, classical assumption tests, and hypothesis testing using simple linear regression with t-test and F-test. The results indicate that strengthening religious moderation has a significant effect on students’ tolerant attitudes, with a significance value of 0.027 (< 0.05). However, strengthening religious moderation does not have a significant effect on students’ religious behavior, as indicated by a significance value of 0.208 (> 0.05). In conclusion, strengthening religious moderation contributes to improving students’ tolerant attitudes but does not significantly influence their religious behavior at As-Syakur Islamic Boarding School, Bengkulu City. Keywords: Religious Moderation, Religious Behavior, Tolerant Attitude